THE IMPACT OF CERTAIN CHEMICAL ELEMENTS IN SOILS ON HUMAN HEALTH IN THE EXAMPLE OF URGUT DISTRICT - Rajabovich, Mirzaliyev Sindor; Yunus Tolib oglu, Karimov; Abdurashid Omonkulovich, Gulomov (Journal of Geography, Regional Planning and Development, 2025)
Objective: This study aims to analyze the presence and concentration of specific radioactive and chemical elements in the soils of the Urgut district and assess their potential impact on human health. Method: A field and laboratory approach was employed, involving soil sample collection from key locations followed by spectral analysis, mass spectrometry, and X-ray fluorescence to determine the levels of dysprosium, erbium, neodymium, and strontium. Results: The findings reveal that concentrations of these elements vary across different geographical areas, with strontium showing particularly high levels in certain regions, potentially posing health risks through soil exposure and food chain contamination. Dysprosium and erbium were found at relatively uniform but concerning levels across foothill and plain areas. Novelty: This research contributes a novel perspective by linking geochemical soil characteristics directly with public health implications in a specific and underexplored region, offering critical insights for regional ecological assessments and the development of localized health safety interventions.